PREWRITING ACTIVITIES USING ASSISTED-TECHNOLOGY IN EFL JOURNALISM: A NEEDS ANALYSIS - Dwi Sloria Suharti; Eka Ugi Sutikno; Hani Dewi Aries Santi (PROJECT (Professional Journal of English Education), 2020)
Analysis of the needs is an imperative pace for curriculum developers in different subjects, including assisted-technology in prewriting activities in EFL Journalism. Needs are required to examine the assisted-technology demanded while EFL learners applied prewriting activities. This study aimed to study assisted-technology necessities in EFL students' prewriting activities at a private university in Indonesia. The study investigated the needs of assisted technology in prewriting activities in EFL Journalism learning. A qualitative description has been developed. Seventy-two students completed the questionnaires, and several students were also interviewed. The result revealed that students are in needs, lacks, and wants assisted-technology in prewriting activities. This study suggests that teachers and universities periodically carry out a needs analysis to develop a curriculum and teaching strategies for all of these reflective needs.